2019 IEEE/AIAA 38th Digital Avionics Systems Conference (DASC) 2019
DOI: 10.1109/dasc43569.2019.9081623
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Drones and their Public Acceptance

Abstract: Any emergent technology in history has raised an initial rejection by part of the society. Added to the several problems that the non-mature technology may have, the lack of any previous experience about side effects and the humans psychological fear to the unknown play an important influence in its acceptance. As drones bring up high social and economic expectations due to their capabilities and bussiness applications, the social acceptance is key to the complete development of drone technology's potential. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…With the tendency to increase the existence of drones and their usage, because they are cheap and easy to use, several conditions and contents need to be legislated. 25 As the authors 27 state the difficulty associated with new technology regarding public acceptance and raising concern of safety and privacy. Several use cases were presented to analyze the balance of social acceptance between the drone's usability and safety and privacy concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the tendency to increase the existence of drones and their usage, because they are cheap and easy to use, several conditions and contents need to be legislated. 25 As the authors 27 state the difficulty associated with new technology regarding public acceptance and raising concern of safety and privacy. Several use cases were presented to analyze the balance of social acceptance between the drone's usability and safety and privacy concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the authors 27 state the difficulty associated with new technology regarding public acceptance and raising concern of safety and privacy. Several use cases were presented to analyze the balance of social acceptance between the drone's usability and safety and privacy concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social Challenges Early on, social challenges associated with commercial drones received great attention by academia and multiple studies already analyzed the public perception of drones in the past (e.g., Eißfeldt and End, 2020;Miethe et al, 2020). In this process, researchers repeatedly argue that the acceptance of drones as a new emerging technology will have a major impact on the success of integration and scaling of commercial use (Macias et al, 2019;Rice et al, 2018). The German Aerospace Center conducted a survey in Germany in 2020 with 832 participants on the acceptance of drone deliveries and showed that 59% of the respondents disapprove drone delivery applications.…”
Section: Operational Challenges While Commercial Dronesmentioning
confidence: 99%
“…Indeed, 'how to make drones more acceptable' underpins a number of the studies discussed above. Maclas et al [46] further highlight the need for inclusiveness and approaches that empower people to get involved in decision making and, as experts build understanding of systems of provision, there will be communication opportunities. While it is relatively easy to show people drones and their capabilities, it is less easy to show them how provision might look in terms of volume of drones, where they might fly, how high/low, how far away, how they might sound.…”
Section: Acceptancementioning
confidence: 99%